Unusual placement of intrathecal baclofen pumps: report of two cases - Devine, Oliver (Acta Neurochir (Wien), 2015)
Intrathecal baclofen delivery via implantable pump represents an important modality for symptomatic relief in patients with chronic spasticity. Pumps are routinely implanted subcutaneously in the anterior abdominal wall. We describe two unusual cases where skin-related complications necessitated revision surgery in order to relocate the pump to alternative sites. The first patient was an international power canoeist, whose strenuous exercise programme interfered with his pump’s original siting. The second patient was a cachectic university student with a history of cerebral palsy, who maintained low body mass despite attempted weight gain. The relocation of these two intrathecal devices to the medial compartment of the right thigh and right iliac fossa, respectively, is described.